Utilization of Mendong Plants-Activated Charcoal as H2S and NO2 Gas Adsorbent: Preliminary Study - Sulistyo Saputro; Rizka Fauzia Hanif; Inung Widyastuti; Lina Mahardiani (The Journal of Pure and Applied Chemistry Research, 2021)
The study of exhaust H2S and NO2 gases using activated carbon has been conducted. In this study, activated carbon was prepared from mendong plant (Frimbistylis umbellaris), which was activated using zinc chloride (ZnCl2) with concentrations of 2.5; 5; 7.5; and 10 % w/v to determine the efficiency of H2S adsorption. Mendong charcoal was obtained from the process of using a modified tool. Activation was done by maceration using ZnCl2 activator (w/v) for 24 hours. The adsorption of H2S and NO2 was analyzed using UV-Vis spectrophotometry. Determinations of H2S gas carried out using the blue methylene’s method for 1 hour showed the highest effectiveness of mendong activated carbon was of that at the concentration of 2.5 % ZnCl2 w/v with 80% of H2S removal. Further, the mendong activated carbon with the concentration of 2.5% ZnCl2 w/v was used for NO2 adsorption. The adsorption of NO2 gas was conducted for 1 hour using Griess Saltzman’s method. The result showed that the largest concentration of NO2 gas was adsorbed when the HNO3 concentration was 1.5 M (0.057 µg/mL). The percentage of NO2 efficiency adsorbed was at 28%.